Rv0954 Is a Member of the Mycobacterial Cell Division Complex - Wang, Ruojun; Ehrt, Sabine (Frontiers in Microbiology, 2021)
Proper control of cell division in the intracellular pathogen Mycobacterium tuberculosis is central to its growth, survival, pathogenesis, and resistance to antibiotics. Nevertheless, the divisome components and mechanisms by which mycobacteria regulate their cell cycle are not entirely understood. Here we demonstrate that the previously uncharacterized Rv0954 protein localizes to the mid-cell during cell division and interacts with the division-related proteins LamA, PbpA, and PknH. Deletion of rv0954 did not result in alterations in cell morphology or sensitivity to cell wall-targeting antibiotics but transposon mutagenesis demonstrated genetic interactions with genes related to cell division. This work suggests that Rv0954 participates in cell division and reveals potential components of the mycobacterial divisome for future investigation.